Colorism and immigrant earnings in the United States, 2015–2024 - Joni Hersch; Joni Hersch (Frontiers in Sociology)
Using data from the Current Populations Survey 2015–2024 matched to skin color data in the New Immigrant Survey, this article shows that immigrants from countries with darker skin color face a substantial earnings penalty. The penalty is similar to that found using 2003 data on individual immigrants. Controls for extensive labor market characteristics and race and ethnicity does not eliminate the negative effect of darker skin tone on wages. Color discrimination lawsuits in light of the addition of a Middle Eastern and North African (MENA) reporting category for US government surveys may become more viable.